Evaluasi Kesesuaian Desain Rumah Tinggal Dua Lantai terhadap Kondisi Iklim dan Kerawanan Gempa di Pulau Lombok - Laras Alencia Eka Putri; Laura Angelica Fadia Indriani; Jelita Bulanisahadi; Nazwa Laily Azzahrah; Agil Fitri Handayani (Jurnal Talenta Sipil, 2026)
Lombok Island has a humid tropical climate and a high risk of earthquakes due to tectonic activity; consequently, residential design must take into account aspects of thermal comfort and structural resilience. This study aims to evaluate the suitability of the architectural and structural design of a two-storey residential house for three occupants in relation to local environmental conditions. The method used is descriptive evaluation with a case study approach by reviewing design drawings, including floor plans, elevations, sections, and structural details, which were then compared with the principles of tropical house design and general provisions for earthquake-resistant buildings. The results of the study indicate that the spatial layout meets the functional needs of a small family with a clear division between private and public zones, whilst applying tropical architectural principles through the use of pitched roofs and natural openings to enhance thermal comfort. However, from a structural perspective, the details of the foundation, columns, beams, and structural connections are not yet sufficiently explained, thus requiring further technical verification based on earthquake-resistant building provisions. Consequently, whilst this house design meets functional and climatic requirements, it does not yet fully comply with earthquake-resistant building principles, thus requiring structural design optimisation.